Navigating the complexity of current interventional radiological approaches for distant metastases in thyroid cancer - Zhang, Daqi; Spisani, Jerry; Ceriello, Arianna; Frattini, Francesco; Brucchi, Francesco; Dionigi, Gianlorenzo; Wan, Lanlan; Angileri, Alessio Salvatore; Colombo, Carla; Ierardi, Anna Maria; Carrafiello, Gianpaolo (Frontiers in Endocrinology, 2025)
The finding of liver metastases in thyroid cancer is relatively uncommon. Treatment is complex and depends on several factors, including location, number and size of lesions, associated symptoms, extrahepatic disease and patient’s condition. In this context, interventional radiological treatments have been successfully used to optimize disease control or for palliative purposes and have generally been well tolerated. However, careful selection of candidates for such procedures in a multidisciplinary context is crucial.